Driving factors of innovation: Dimensions of open culture and conscious innovation management in the environmental context - Elvira, Verens; Kusumastuti, Retno (Journal of Character and Environment, 2025)
Background: Innovation is crucial for advancing businesses, organizations, and countries, especially amid rapid environmental changes and technological advancements. Universities, as key sources of innovation, must shift to include societal contributions. Despite progress, challenges in commercialization hinder the effective translation of research into marketable products. This study explores the driving factors of innovation at Universitas Indonesia, focusing on open culture and conscious innovation management in an environmental context. Methods: This study utilizes an embedded mixed-methods design, primarily focusing on quantitative research to analyze driving factors of innovation at Universitas Indonesia, employing descriptive analysis through SPSS software for data interpretation. Findings: This section analyzes the driving factors of the innovation process at the Universitas Indonesia, focusing on respondents' perceptions of collaboration, governance, communication, and financial motivation, highlighting areas for improvement. UI demonstrates high cooperation with the business sector but requires more dynamic regulations for effective collaboration. The Dimension of Conscious Innovation Management at UI demonstrates professionalism in innovation management; however, there are still challenges related to program regulations. Conclusion: Universitas Indonesia should enhance collaboration, establish structured remuneration, and allow flexible SOPs to foster sustainable innovation. Novelty/Originality of this article: This study uniquely investigates the interplay of cultural openness and conscious innovation management at Universitas Indonesia, offering practical recommendations to enhance commercialization and sustainability in the university's innovation processes.